Hyperoxia enhances self-paced exercise performance to a greater extent in cool than hot conditions - Périard, J. D.; Houtkamp, D.; Bright, F.; Daanen, H. A. M.; Abbiss, C. R.; Thompson, K. G.; Clark, B. (Experimental Physiology, 2019)
What is the central question of this study?